SPE Annual Technical Conference and Exhibition 2000
DOI: 10.2118/63156-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Fully Compositional Streamline Simulator

Abstract: A new 3-D three phase compositional reservoir simulator based on extension of the streamline method has been developed. This paper will focus on the new methods developed for compositional streamline simulation as well as the advantages and disadvantages of this strategy compared with more traditional approaches. Comparisons with a commercially available finite difference simulator will both validate the method and illustrate the cases in which this method is useful to the reservoir engineer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 61 publications
0
32
0
Order By: Relevance
“…The streamline method is similar to an implicit pressure, explicit saturations approach for oil-water or black-oil systems, or an implicit pressure, explicit compositions approach for compositional problems [8,29], with the difference that the transport equations are solved on the specialized transport grid formed by the streamlines. The two distinct time step sizes in this process are the time step between pressure updates (the global time step) and the time step used in the numerical transport solve along streamlines to move saturations or compositions between pressure updates (the local time step).…”
Section: The General Streamline Simulation Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The streamline method is similar to an implicit pressure, explicit saturations approach for oil-water or black-oil systems, or an implicit pressure, explicit compositions approach for compositional problems [8,29], with the difference that the transport equations are solved on the specialized transport grid formed by the streamlines. The two distinct time step sizes in this process are the time step between pressure updates (the global time step) and the time step used in the numerical transport solve along streamlines to move saturations or compositions between pressure updates (the local time step).…”
Section: The General Streamline Simulation Processmentioning
confidence: 99%
“…The computational efficiency of streamline methods for many-reservoir settings make them especially suitable for history matching and optimization problems, and commercial streamline simulators are applied for such purposes. Streamline simulation has recently been extended to handle (near-) miscible gas injection processes [8,29], as well as flow in fractured reservoirs [11].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the improved mappings discussed in the previous section reduce smoothing and mass balance errors so that more frequent pressure updates are acceptable if needed. Ingebrigtsen et al (1999) and Crane et al (2000) suggested updating the pressure along streamlines during a global time step to better honor the strong coupling between the pressure and transport equations. For gas injection problems, a similar approach may help to account for volume change at gas fronts.…”
Section: An Adaptive Streamline Frameworkmentioning
confidence: 99%
“…Gas displacement processes are one of the critical areas in SL simulation, as the compressibility remains a significant issue. Crane et al [26] used 1D fully implicit solutions of FD simulation to solve for pressure and fluid compositions together along each streamline, and account for the changes of the phase behavior that depend on the changes in pressure. It was tested and compared against FD compositional simulator using the SPE 9 Model.…”
Section: Introductionmentioning
confidence: 99%